Assessment of proteolysis and lipolysis in Serra cheese: effects of axial cheese location, ripening time and lactation season - Macedo, A. C. (2011)
The degrees of proteolysis and Iipolysis in Serra cheese were measured in cheese samples obtained from experiments laid out as a three-way facto rial design replicated twice. The independent variables studied were the location within the cheese (from the center to the surface), the position in the lactation season (from October to June) and the ripening time (from 0 to 35 days). Ali three variables had statistically significant effects on the concentration of water soluble peptides (WSP), but only the ripening time and the period within the lactation season affected the fat acidity (FA). The extents (alter the given ripening period) and the rates (averaged over the ripening period) of generation of WSP and FA were highest for spring and lowest for autumn. The lowest values for both the proteolysis extent and the proteolysis rate were obtained for the rind. The rates of proteolysis and lipolysis tended to decrease with ripening time; most of the lipolysis occurred during the first week, but proteolysis was still in progress by 35 days of ripening.